AB0416 Reliability and Safety of A Novel Autoinjector for Self-Administration of Subcutaneous Belimumab in Patients with Systemic Lupus Erythematosus (SLE). (15th July 2016) - Sheikh, S.Z.; Fox, N.L.; Hammer, A.E.; Struemper, H.; Groark, J.; Roth, D.; Gordon, D.
Abstract : Background: The ability to self-administer subcutaneous (SC) belimumab would enhance treatment options for patients with SLE. Objectives: The reliability and safety of a novel autoinjector for self-administration of belimumab SC was examined in patients with SLE. Methods: Study 200339 (NCT02124798 ) enrolled adults with SLE who had received at least three prior intravenous (IV) doses of belimumab 10 mg/kg plus standard care, or who had completed the open-label continuation phase of a randomised, controlled trial of belimumab SC (prefilled syringe). Open-label belimumab 200 mg SC (1 mL) was self-administered weekly (thigh or abdomen) using an autoinjector, under clinic observation at Weeks 1, 2, 4, 8 and at home at Weeks 3, 5, 6, 7. Patients assessed and recorded injections using a diary. Investigators assessed clinic injections. The primary endpoint was the proportion of patients who successfully administered the first two injections. Secondary endpoints included success at Weeks 4 and 8 within the clinic and success at Weeks 3, 5, 6, and 7 at home. Results: 95 patients enrolled: 91 completed the study (3 withdrew due to AEs, 1 patient was lost to follow-up). 88 (93%) patients were female; mean (SD) age was 44.8 (12.5) years. Overall, 94% (89/95) of patients successfully administered belimumab at Weeks 1 and 2 using the autoinjector. Five patients completed their 1st injection with assistance from clinic personnel. Of 736 attempted injections 720 (98%) were considered to be successful. Of the 16 injections reported to be incomplete, 14 (4 from 1 patient) were associated with use errors, 13 of which were concluded to be related to not holding the autoinjector in place until the injection was completed. Use errors were repeated by only 1 patient. Reported pain levels were low and diminished over time. A total of 39 (41%) patients reported at least one adverse event (AE) and 15 (16%) patients reported an AE considered to be drug related. Four (4%) patients reported 7 serious AEs: anaemia/neutropenia/pneumonia/pyrexia, postoperative abscess, pulmonary embolism and deep vein thrombosis. Four (4%) patients reported injection site reactions: erythema (2), pruritus, rash, injection-related reaction and site reaction. No serious systemic reactions or deaths were reported. Conclusions: Patients with SLE successfully administered belimumab SC using a novel autoinjector. Acknowledgement: Study funded by GSK. Louisa Pettinger, PhD, Fishawack Indicia Ltd, provided submission assistance, funded by GSK. Disclosure of Interest: S. Sheikh: None declared, N. L. Fox Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, A. Hammer Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, H. Struemper Shareholder of: GlaxoSmithKline, Employee of: PAREXEL, J. Groark Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Roth Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Gordon Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline